Halloysite Nanotubes/Natural Rubber (Hnts/Nr) Nanocomposites: Preparation And Properties - Salleh, Siti Zuliana (2012)
This research focused on the effect of various HNTs loading on the properties of natural rubber nanocomposites. Series (1), HNTs filled in two types of natural rubber i.e., unmodified and modified natural rubber namely SMR L and ENR 50 respectively were investigated. In Series (2), the study of partial replacement of HNTs with carbon black (CB) as hybrid fillers was studied. Lastly in Series (3), the study regarding different type of mixing methods i.e., mechanical and solution mixing methods were compared. Conventional vulcanization (CV) system has been selected in this research and laboratory two-roll mill was used for mixing process. The studied properties in this research includes curing characteristics, mechanical properties, swelling percentage, fatigue life, thermal stability and morphological properties of HNTs filled natural rubber. Mosanto Moving Die Rheometer (MDR 2000) with temperature at 150°C was used to determine curing characteristics for nanocomposites. In Series (1), optimum tensile strength of HNTs/SMR L and HNTs/ENR 50 nanocomposites was achieved with 20 phr. Thermal stability increased with addition of HNTs in both nanocomposites. In Series (2), tensile strength, tensile modulus and thermal stability of nanocomposites increased. In Series (3), solution mixing method nanocomposites showed higher tensile strength, tensile modulus and fatigue life at any HNTs loading. Generally, the SEM images showed that lower HNTs loading can be dispersed uniformly in matrix but bad and poor dispersion was observed at higher HNTs loading.